Modeling Fiber Fineness, Maturity, and Micronaire in Cotton (Gossypium hirsutum L.) - Wen-qing ZHAO; Zhi-guo ZHOU; Ya-li MENG; Bing-lin CHEN; You-hua WANG (Journal of Integrative Agriculture, 2013)
Crop performance is determined by the combined effects of the genotype of the crop and the environmental conditions of the production system. This study was undertaken to develop a dynamic model for simulating environmental (temperature and solar radiation) and N supply effects on fiber fineness, maturity and micronaire. Three different experiments involving genotypes, sowing dates, and N fertilization rates were conducted to support model development and model evaluation. The growth and development duration of fiber fineness, maturity, and micronaire were scaled by using physiological development time of secondary wall synthesis (PDTSWSP), which was determined based on the constant ratio of SWSP/BMP. PTP (product of relative thermal effectiveness (RTE) and photosynthetically active radiation (PAR), MJ m−2) and subtending leaf N content per unit area (NA, g m−2) and critical subtending leaf N content per unit area (CNA, g m−2) of cotton boll were calculated or simulated to evaluate effects of temperature and radiation, and N supply. Besides, the interactions among temperature, radiation and N supply were also explained by piecewise function. The overall performance of the model was calibrated and validated with independent data sets from three field experiments with two sowing dates, three or five flowering dates and three or four N fertilization rates for three subsequent years (2005, 2007, and 2009) at three ecological locations. The average RMSE and RE for fiber fineness, maturity, and micronaire predictions were 372 m g−1 and 5.0%, 0.11 m g−1 and 11.4%, 0.3 m g−1 and 12.3%, respectively, indicating a good fit between the simulated and observed data. It appears that the model can give a reliable prediction for fiber fineness, maturity and micronaire formation under various growing conditions.